Beyond deep-sea mining sublethal effects: Delayed mortality from acute Cu exposure of the cold-water octocoral Viminella flagellum. (October 2022) - Martins, Inês; Godinho, António; Rakka, Maria; Carreiro-Silva, Marina
Abstract: The potential release of metals, especially copper (Cu) during mining of seafloor massive sulphides (SMS), represents a potential toxicological threat to cold-water coral (CWC) habitats. Herein, we evaluated for the first time the response of the whip coral Viminella flagellum to short-term acute Cu exposure. Nubbins of V . flagellum were exposed to Cu concentrations of 0 (control); 60; 150; 250; 450 and 600 μg/L for 96 h. After exposure, V . flagellum nubbins were transferred to a continuous flow-through aquarium and feed once a day for 3 weeks. No immediate mortality was detected during the short-term Cu exposure. However, a delayed mortality, which was concentration dependent was observed. The first signs of tissue loss occurred after 1 week of recovery in non-contaminated conditions in V . flagellum nubbins previously exposed to Cu concentrations of 60 and 150 μg/L followed by nubbins exposed to Cu concentrations of 250, 450 μg/L after 2 weeks and 600 μg/L after 3 weeks. A delayed mortality impact should be considered in future Cu tolerance experiments and scenarios of deep-sea mining exploitation. Graphical abstract: Unlabelled Image Highlights: No immediate mortality was observed after a 96 h exposure. Cu exposure caused elevated metabolic rates in Viminella flagellum . Delayed mortality occurred after 1 to 2 weeks in non-contaminated conditions. No recovery was observed in any of the Cu exposures. It is important to monitor and revisit impacted CWC ecosystems.